The influence of the sinonasal microbiome on the development and management of rhinosinusitis - Lang, Miriam; Bereza, Dawid; Kulak-Waśniewska, Maria; Moreau, Igor; Polańska, Paulina; Sokołowska, Katarzyna; Woch, Barbara (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Chronic rhinosinusitis (CRS) is a frequently diagnosed condition in patients seeking medical care. It encompasses a range of disorders that can be classified based on underlying causes, clinical symptoms, or inflammatory types. Although the precise cause of CRS remains unclear, the European Position Paper on Rhinosinusitis and Nasal Polyps 2020 (EPOS 2020) has recently offered updated insights, treatment strategies, and recommendations. State of knowledge: Recent research has increasingly focused on the role of the microbiota in inflammatory diseases. The optimal bacterial environment in the sinonasal mucosa, where inhaled bacteria, viruses, fungal spores, and particles initially interact, is still not fully understood. The dysbiosis theory, which emphasizes the importance of the microbiome and its relationship with the host, is the predominant model explaining CRS pathogenesis. Disruptions in this balance can lead to a variety of clinical manifestations in CRS patients. Conclusions: Given the impact of CRS treatment on the composition of sinus and nasopharyngeal microbiota, the dysbiosis theory highlights the importance of addressing this aspect in therapeutic strategies. Ongoing research is exploring the potential use of pre- and probiotics as novel treatment options. A more thorough understanding of the microbiological factors involved in CRS is crucial for developing personalized, targeted therapies for affected individuals.